The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1063/1.2208375
|View full text |Cite
|
Sign up to set email alerts
|

Overannealing effects in GaInNAs(Sb) alloys and their importance to laser applications

Abstract: The photoluminescence efficiency and linewidth are well-established metrics for characterizing potential laser active regions. We demonstrate the critical importance of a new parameter for predicting the performance of dilute-nitride lasers: the “optimal” postgrowth annealing temperature, defined as the annealing temperature giving the highest photoluminescence efficiency. We validate this assertion with two 1.55μm edge-emitting GaInNAsSb lasers containing active regions with different optimal annealing temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…This result is very striking, in that it runs contrary to all earlier reports of rapid degradation with increasing nitrogen content. We have found that adding more nitrogen is a better way of extending laser wavelength than adding indium [86], resulting in the lowest threshold 1.55 µm dilute nitride lasers to date.…”
Section: Wwwpss-bcommentioning
confidence: 96%
See 2 more Smart Citations
“…This result is very striking, in that it runs contrary to all earlier reports of rapid degradation with increasing nitrogen content. We have found that adding more nitrogen is a better way of extending laser wavelength than adding indium [86], resulting in the lowest threshold 1.55 µm dilute nitride lasers to date.…”
Section: Wwwpss-bcommentioning
confidence: 96%
“…In our case the lasing wavelength was successfully extended to 1.55 µm by increasing the nitrogen content [89]. It is worth noting that our initial attempts to extend the wavelength by increasing indium content were less successful, resulting in higher threshold current density, even though the optical quality of the PL sample was equivalent [86]. We suggest that the higher-indium GaInNAsSb active regions are damaged by the in-situ anneal during laser growth, and their weak thermal robustness is evidenced by the lower optimal anneal temperature of the PL samples.…”
Section: Gainnassb High Power Edge-emitting Lasersmentioning
confidence: 96%
See 1 more Smart Citation
“…Annealing is well-known to significantly improve the optical quality of dilute nitrides, but also severe degradation by overannealing has been reported [12]. The As flux has been shown to be one of the most important growth parameters during growth of GaInNAs QWs [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This has persuaded many investigators to deal with dilute nitride alloys (i.e., Ga 1−y In y N x As 1−x , with a nitrogen concentration x ≤ 6%) [8,9], in order to avoid lattice-distortion problems. The result is an almost exclusive concentration on telecommunication applications for * Tel.…”
Section: Introductionmentioning
confidence: 99%